Impact of corticosteroid administration on the response of exposed dental pulp to capping with bioactive cements-experimental study on mongrel dogs - Hanan A. Soliman; Radwa Ibrahim EL-Toukhy; Mona Mohsen Abdo Ibrahim; Mohammed E. Grawish; Mohamed Abdel kader Sobh; Salah Hasab Mahmoud (BMC, 2023)
Abstract Background Corticosteroids are commonly used as a treatment for a variety of pathological conditions, however, systemic corticosteroid administration has adverse effects including impaired immune response and wound healing. Such complications may affect pulp healing after direct pulp capping. The current study evaluated the influence of corticosteroids on the healing ability of exposed dogs' dental pulps after direct pulp capping (DPC) with bioactive materials. Methods Ten healthy male dogs were assigned randomly into two groups, 5 dogs each: group I represent the control group which did not receive any medication, and group II was given corticosteroid for 45 days before DPC and till the dogs were euthanized (n = 75 teeth for each group). Following mechanical exposure, the pulps were randomly capped with either Ca(OH)2, MTA, or Biodentine. The pulpal tissues' reaction to the capping materials was evaluated 65 days postoperatively according to the following parameters: calcific bridge formation, pulpal inflammation, pulp necrosis, and bacterial infiltration. Results The corticosteroid-treated group revealed no significant difference compared to the control group concerning the pulp healing response (P > 0.05). Both Biodentine and MTA-treated specimens revealed significant differences with Ca(OH)2-treated specimens (P < 0.05) which displayed a superior positive effect of both MTA and Biodentine to Ca(OH)2 regarding all the parameters. Conclusions Direct pulp capping technique whenever indicated in subjects treated with corticosteroid immunosuppressive drugs like prednisone performed well in aseptic conditions especially when capped with bioactive materials.